Inhibition of Glutamate Release from Rat Cortical Nerve Terminals by Dehydrocorydaline, an Alkaloid from Corydalis yanhusuo - Lin, Tzu-Yu; Chen, I-Yen; Lee, Ming-Yi; Lu, Cheng-Wei; Chiu, Kuan-Ming; Wang, Su-Jane (Molecules (Basel, Switzerland), 2022)
Excessive release of glutamate induces excitotoxicity and causes neuronal damage in several neurodegenerative diseases. Natural products have emerged as potential neuroprotective agents for preventing and treating neurological disorders. Dehydrocorydaline (DHC), an active alkaloid compound isolated from Corydalis yanhusuo, possesses neuroprotective capacity. The present study investigated the effect of DHC on glutamate release using a rat brain cortical synaptosome model. Our results indicate that DHC inhibited 4-aminopyridine (4-AP)-evoked glutamate release and elevated intrasynaptosomal calcium levels. The inhibitory effect of DHC on 4-AP-evoked glutamate release was prevented in the presence of the vesicular transporter inhibitor bafilomycin A1 and the N- and P/Q-type Ca2+ channel blocker ω-conotoxin MVIIC but not the intracellular inhibitor of Ca2+ release dantrolene or the mitochondrial Na+/Ca2+ exchanger inhibitor CGP37157. Moreover, the inhibitory effect of DHC on evoked glutamate release was prevented by the mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) inhibitor PD98059. Western blotting data in synaptosomes also showed that DHC significantly decreased the level of ERK1/2 phosphorylation and synaptic vesicle-associated protein synapsin I, the main presynaptic target of ERK. Together, these results suggest that DHC inhibits presynaptic glutamate release from cerebrocortical synaptosomes by suppressing presynaptic voltage-dependent Ca2+ entry and the MAPK/ERK/synapsin I signaling pathway.